Tantangan dan Strategi dalam Membangun Keterbukaan Informasi - Aprianto, Yudie; Idowu, Olumayowa Adeleke (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Despite the importance of information transparency, many institutions face underappreciated challenges when implementing transparent practices. This study seeks to systematically identify barriers to information openness and proposes actionable strategies to address them. This study utilizes a qualitative approach to uncover multifaceted public information challenges. The findings advocate for an integrated approach to overcoming these hurdles. Key recommendations include establishing adaptive data governance protocols aligned with evolving legal standards, adopting scalable technologies that prioritize both accessibility and security, and cultivating organizational cultures that reframe transparency as a shared responsibility rather than a risk. The study concludes that sustained transparency requires ongoing adaptation to technological advancements and societal expectations, positioning it not as a static goal but as a dynamic component of organizational resilience. Implications: By embracing these challenges, organizations can successfully navigate the complexities of information transparency and gain the advantages of enhanced stakeholders’ relationships and informed decision-making.